Teacher Ethics in Coding and Artificial Intelligence (AI) Learning in Primary and Secondary Education - Lilik Binti Mirnawati; Aswin Rosadi (Universitas Pendidikan Ganesha, 2025)
Digital transformation in education has driven the integration of coding and artificial intelligence (AI) into learning at the primary and secondary levels. This integration presents complex ethical challenges, particularly in ensuring the teacher's role as a moral guide in technology-based instruction. This study aims to analyze the role of teacher professional ethics in coding and AI education and to evaluate emerging ethical issues, such as algorithmic bias, privacy violations, and digital access inequality. The research subjects include a collection of scientific literature obtained from academic journals, reference books, and relevant policy documents. This study employs a qualitative descriptive approach with a literature review method and thematic analysis techniques. The findings indicate that teachers are not only responsible for delivering technical content but also play a crucial ethical role in cultivating students’ social awareness regarding the moral implications of technology. The study concludes that strengthening teacher ethics through continuous training and integrating digital ethics into the curriculum is essential. The implications point to the urgency of adaptive educational policies in response to the ethical dynamics of AI-based learning.